The effect of regional tax and regional retribution on regional expenditure in local governments of North Sumatera Province - Heny Triastuti Kurnia Ningsih (Proceedings of AICS - Social Sciences, 2017)
The purpose of this research is to examine the significant impact of Regional Tax and Regional Retribution to Regional Expenditure in Regency/City at North Sumatera Province. The method used is using time series data design with 33 Regency/City consisting of 25 Regency and 8 City at North Sumatera Province as a sample. This research is done for 2012-2015 period. This research utilizes secondary data. The data are taken from Badan Pusat Statistik (BPS) of North Sumatera Province. The data which is analyzed in this research are collected through the region budget of Revenue and Expense and the realization region budget of Revenue and Expense. The data which have already collected are processed with classic assumption test before hypothesis test. Hypothesis test in this research use double regression with partially test (t test), simultaneously test (F test) and coefficient determination test (R2). The result of this research shows that partially Regional Tax and Regional Retribution have a positive significant impact to the Regional Expenditure in Regency/City at North Sumatera Province. Local Tax and Local Retribution have a positive significant impact to the Local Expenditure in Regency/City at North Sumatera Province.